Fluorescence Investigations into Complex Coacervation between Polyvinylimidazole and Sodium Alginate - Srivastava, Aasheesh (2009)
Electrostatic interactions between the imidazole-based cationic homopolymer, polyvinylimidazole (PVIm), and anionic polysaccharide, sodium alginate, lead to the formation of colloidal aggregates known as complex coacervates in the pH range 4–6.5. PVIm was labeled with the fluorescent reporter pyrene to investigate the coacervation-induced changes in and around PVIm chains. While the pyrene-tagged PVIm had blue fluorescence in water, the coacervate phase exhibited an additional broad band around 492 nm (green) due to formation of pyrene excimers. Fluorescence spectroscopic investigations point toward aggregation of PVIm chains and desolvation upon coacervation. Highly anisotropic fluorescence emission indicates tight packing of the polymer chains in the coacervate. Confocal microscopy of fluorescein-labeled alginate and rhodamine-labeled PVIm shows coacervates as dense aggregates with uniform distribution of the polymers. Fluorescence spectroscopy offers sensitive and easy investigation into polyelectrolyte interactions.